SOCIAL, CULTURAL, ECONOMIC AND DEMOGRAPHIC FACTORS INFLUENCING AI REGULATION IN KAZAKHSTAN - Tokhtakhounov B.N. (Theoretical Hypotheses and Empirical Results, 2025)
The article analyzes the social, cultural, economic, and demographic factors that shape the specifics of artificial intelligence (AI) regulation in Kazakhstan, using the example of the Republic of Kazakhstan Law "On Artificial Intelligence" dated November 17, 2025. The author emphasizes that the new law reflects the transitional nature of Kazakhstani society: the post-Soviet legacy of distrust in institutions, multi-ethnic and nomadic cultural diversity, the economy's dependence on oil, and a young demography with a pronounced digital divide between urban and rural areas. A comparison is made between the Kazakhstani approach and the models of the European Union (EU AI Act, focused on protecting individual rights and strict risk classification) and China (state-centered ethics with an emphasis on social harmony and control). The advantages of Kazakhstan's hybrid model are identified, allowing the combination of innovation with social justice and cultural sensitivity. Threats are discussed the intensification of inequality and decline in trust due to insufficient attention to local specifics and measures to minimize them are proposed: public consultations, cultural audits of AI, digital literacy programs, and independent oversight. The article demonstrates that successful AI regulation in Kazakhstan is possible only when national characteristics are taken into account, making the country a potential leader in Central Asia in creating an inclusive and humane model of digitalization.